Theorizing crime & deviance : a new perspective - Hall, Steve (SAGE, 2012)
"Steve Hall uses cutting-edge philosophy and social theory to analyze empirical work on patterns of crime and illuminate contemporary criminological issues. He provides a fresh, relevant critique of the philosophical and political underpinnings of criminological theory and the theoretical canon's development during the twentieth century. Unmatched in its sophistication yet written in a clear, accessible style, this dynamic and highly engaging book is essential reading for all students, researchers and academics working in criminology, sociology, social policy, politics and the social sciences in general." -- Publisher's website.